Real-Time Quartz Crystal Microbalance Monitoring of Free Docosahexaenoic Acid Interactions with Supported Lipid Bilayers - Flynn, Kiera R (Langmuir : the ACS journal of surfaces and colloids, 2016)
Docosahexaenoic acid (DHA) is the most abundant polyunsaturated omega-3 fatty acid found in mammalian neuronal cell membranes. Although DHA is known to be important for neuronal cell survival, little is know about how DHA interacts with phospholipid bilayers. This study presents a detailed quartz crystal microbalance with dissipation monitoring (QCM-D) analysis of free DHA interactions with individual and mixed phospholipid supported lipid bilayers (SLB). DHA incorporation and subsequent changes to the SLBs viscoelastic properties were observed to be concentration-dependent, influenced by the phospholipid species, the headgroup charge, and the presence or absence of calcium ions. It was observed that 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) SLBs incorporated the greatest amount of DHA concentration, whereas the presence of phospholipids, phosphatidylserine (PS), and phosphatidylinositol (PI) in a POPC SLB significantly reduced DHA incorporation and changed the SLBs physicochemical properties. These observations are hypothesized to be due to a substitution event occurring between DHA and phospholipid species. PS domain formation in POPC/PS 8:2 SLBs was observed in the presence of calcium ions, which favored DHA incorporation to a similar level as for a POPC only SLB. The changes in SLB thickness observed with different DHA concentrations are also presented. This work contributes to an understanding of the physical changes induced in a lipid bilayer as a consequence of its exposure to different DHA concentrations (from 50 to 200 μM). The capacity of DHA to influence the physical properties of SLBs indicates the potential for dietary DHA supplementation to cause changes in cellular membranes in vivo, with subsequent physiological consequences for cell function